DESAIN KERANGKA MOBILE LEARNING MANAGEMENT SYSTEM (M-LMS) PADA PERGURUAN TINGGI: MOBILE LEARNING MANAGEMENT SYSTEM, ONLINE LEARNING, THE FRAME WORK DESIGN - Rini, Faiza; Weay, Angling (FORTECH (Journal of Information Technology), 2018)
This article focused on frame work design of the Mobile Learning Management System (M-LMS) in universities that can increase knowledge, creativity and motivation in learning. The frame work design of the M-LMS consists of Learning content, learning evaluation, knowledge and interfaces that support online learning activities. Learning content can be divided into 3 namely content settings, content delivery and collaboration. The development of internet network technology leads to an increase in the conventional classroom learning process into mobile learning. So that it can increase motivation for creativity and collaboration in learning.